4a-3=2a-1

Simple and best practice solution for 4a-3=2a-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4a-3=2a-1 equation:


Simplifying
4a + -3 = 2a + -1

Reorder the terms:
-3 + 4a = 2a + -1

Reorder the terms:
-3 + 4a = -1 + 2a

Solving
-3 + 4a = -1 + 2a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-2a' to each side of the equation.
-3 + 4a + -2a = -1 + 2a + -2a

Combine like terms: 4a + -2a = 2a
-3 + 2a = -1 + 2a + -2a

Combine like terms: 2a + -2a = 0
-3 + 2a = -1 + 0
-3 + 2a = -1

Add '3' to each side of the equation.
-3 + 3 + 2a = -1 + 3

Combine like terms: -3 + 3 = 0
0 + 2a = -1 + 3
2a = -1 + 3

Combine like terms: -1 + 3 = 2
2a = 2

Divide each side by '2'.
a = 1

Simplifying
a = 1

See similar equations:

| 9y+11x= | | 6m+22=4 | | UV-9V= | | 2(2q+3)=3(4q-2) | | 6b^2-28b+16=0 | | 7(x+3)=40 | | 2(2p-3)=5(p-1) | | 27y-8+9y=-11+17y | | 17y/30-2=4-6y/5 | | D^3-D^2+2=0 | | -2a-3a+3b+2b=28 | | -x^2-12x-29=0 | | P*P=121 | | 5c+.2a+1.5c= | | 0=-x^2+2x-2 | | 7x+31=52 | | 25=14 | | 5c=a | | a=3c+2c | | -5x+3x=16-3x | | x+x-3=15 | | (-12+18x+12x^2)=50x | | 6(4-z)=2(2z+9) | | (12x-6)(x+2)=0 | | 50x^2+88x+6=0 | | 5(2x-1)=5 | | (12-6x)(x+2)=50 | | 60x+40(180-x)=8700 | | (12+6i)-(9+4i)=0 | | 170+3x=100+5x | | 7(3n+1)=9(4n+1)+6 | | -10+2y-4x=0 |

Equations solver categories